INTEGRASI KURIKULUM 2013 DALAM MATA PELAJARAN BAHASA ARAB DI MADRASAH ALIYAH NU TASYWIQUTH THULLAB SALAFIYAH (TBS) KUDUS JAWA TENGAH - Nur Khamim (Intelegensia : Jurnal Pendidikan Islam, 2018)
Abstract:This research describes 2013 curriculum integration in Arabic subject in Madrasah Aliyah NU Tasywiquth Thullab Salafiyah (TBS) Kudus. This research used qualitative approach with the type of descriptive research. Research location is in MA NU Tasywiquth Thullab Salafiyah (TBS) Kudus. Subject in this research was teachers, students, meanwhile the informant was headmaster, vice principal of students, teachers, and students’ parents. The method of collecting data was through observation, interview, and documentation. Research data analysis was using descriptive analysis. Its process was done since collecting data, so in field researcher had begun the analysis process till the end of research. This research concluded that: all Core Competence and Basic Competence of all subjects including Arabic should be aligned and integrated to vision of Madrasah Aliyah NU Tasywiquth Thullab Salafiyah (TBS) Kudus, that is: tough in faith and taqwa, excellent in science and technology, advanced in achievement, and knowledgeable of Islam Ahlussunnah wal-Jama’ah.Keywords: 2013 curriculum integration, Arabic subject